Childhood drowning and traditional rescue measures: case study from Matlab, Bangladesh. Issue 7 (11th March 2011) - Borse, N N; Hyder, A A; Streatfield, P K; Arifeen, S E; Bishai, D
Abstract : Recent mortality data indicate that approximately half a million people drown each year worldwide, with more than 97% of such deaths occurring in low-income and middle-income countries. The purpose of this study was to examine verbal autopsy data on the circumstances of childhood drowning in Matlab, Bangladesh. The study analysed 10 years (1996–2005) of data which reported 489 deaths in children under 5 years and recorded preimmersion, immersion and postimmersion events. The data summarised household characteristics, age, gender and time of drowning event. The study also examined traditional rescue methods performed on children who were removed from the water OR found drowning. Of 489 deaths, 57% were aged 1–2 years and had a drowning mortality rate of 521 per 100 000 children. Most drowning events occurred during the morning (68%), in ponds (69%), and while the mother was busy doing household chores (70%). Traditional rescue methods were attempted in 55% of children and the most frequently reported measure was to spin the child over head (35%). Only 3% of families tried to perform resuscitation. Verbal autopsy data for Matlab is a useful resource for childhood injury research in a low-income country. The study is one of the first to publish data on traditional rescue practices performed on drowning children in rural Bangladesh. The findings suggest that interventions should be designed using locally identified risk factors to reduce childhood drowning incidents. Community-based resuscitation techniques and emergency medical systems are needed to improve postimmersion recovery of the child.